The visual neuroscience of robotic grasping : achieving sensorimotor skills througyh dorsal-ventral stream integration /: achieving sensorimotor skills througyh dorsal-ventral stream integration. ([2016]) - Chinellato, Eris; Pobil, Angel Pasqual del
No abstract available